The Influence of Organizational Trust and Job Satisfaction on Patient Safety Culture with Interprofessional Collaboration as an Intervening Variable - Kurnia Ramadhan; MF Arrozi Adhikara; Sandra Dewi (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The implementation of patient safety culture in hospitals remains a significant challenge, often leading to adverse events. Establishing a strong patient safety culture requires effective interprofessional collaboration among healthcare professionals to deliver patient-centered care. However, factors such as organizational distrust and job dissatisfaction continue to hinder collaborative efforts and negatively affect the quality of care and patient safety outcomes.This study aims to examine the influence of organizational trust and job satisfaction on patient safety culture, with interprofessional collaboration serving as an intervening variable at MP hospital.  This quantitative associative research used a causal approach involving 93 inpatient nurses as respondents. Primary data were obtained through questionnaires using an ordinal scale based on a 4–1 Likert scale. Data processing employed the three-box method, and data analysis was conducted using Structural Equation Modeling (SEM).The results revealed that organizational trust, job satisfaction, and interprofessional collaboration simultaneously and partially influence patient safety culture. Moreover, interprofessional collaboration was found to mediate the relationship between organizational trust, job satisfaction, and patient safety culture.The study concludes that enhancing patient safety culture can be achieved by strengthening organizational trust and job satisfaction through effective interprofessional collaboration. Hospitals should develop supportive systems that foster care and concern among staff, enhance conflict management, improve performance appraisal mechanisms, and promote open, effective communication across all professional groups involved in patient care. These strategies can create a safer, more collaborative, and high-quality healthcare environment